2003
DOI: 10.1111/j.1365-4632.2004.01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin diseases in Ibadan, Nigeria

Abstract: Allergic conditions have increased; connective tissue disorders, such as systemic lupus erythematosus, scleroderma, and discoid lupus erythematosus, have also increased. Cutaneous disorders associated with human immunodeficiency virus infection, such as seborrheic dermatitis, have increased. Health workers need to be educated on the management and treatment of these conditions, and should be advised to refer patients to appropriate health facilities when necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
100
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 25 publications
28
100
12
Order By: Relevance
“…Lower rates of leprosy were reported: Tunisia (0.004%) (21), Cairo (0.08%) (14), Kaduna (Nigeria) (0.1%) (8) and Bandar Abbas (Iran) (0.3%) (25). Higher rate of leprosy (1.2%) was reported in Ibadan (Nigeria) (26). Also, in Assiut, a rate of 5.14% was reported by Abdel-Rehim et al (16).…”
Section: Infective Skin Diseasesmentioning
confidence: 84%
See 2 more Smart Citations
“…Lower rates of leprosy were reported: Tunisia (0.004%) (21), Cairo (0.08%) (14), Kaduna (Nigeria) (0.1%) (8) and Bandar Abbas (Iran) (0.3%) (25). Higher rate of leprosy (1.2%) was reported in Ibadan (Nigeria) (26). Also, in Assiut, a rate of 5.14% was reported by Abdel-Rehim et al (16).…”
Section: Infective Skin Diseasesmentioning
confidence: 84%
“…In Nigeria (Ibadan) a rate of 30.2% was observed (26). It was the second common group in Iran (24.5%) (25).…”
Section: Non-infective Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Community-based studies in Nigeria have reported prevalence rates of skin diseases (or dermatophytoses alone) between 10% and 64%. 1,13,[22][23][24][25][26][27] The most common skin condition was fungal infections, especially tinea capitis among school-age children, especially boys, accounting for 43% of the skin diseases in the community.…”
mentioning
confidence: 99%
“…Since these patterns can vary from one country to another and even within a single city, as they suffer influences of genetic, racial, nutritional, cultural, climatic, social and economic factors, there is a need for local studies. 10 The frequency of diseases in a region may be determined by large-scale population surveys, but these are difficult to conduct because they are timeconsuming and expensive. 11 Studies in ambulatory and hospital services, despite not reflecting the exact situation of a disease in the community, provide indicators of the magnitude of the problem and can be used to develop strategies for its control.…”
Section: Introductionmentioning
confidence: 99%